2021
DOI: 10.1364/prj.427458
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent dynamical state switching in discrete-mode semiconductor lasers subject to optical feedback

Abstract: Hawliau Cyffredinol / General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research.• You may not further distribute the material or use it for any profit-maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…These salient features undoubtedly imply that DM lasers are a good candidate for P1-dynamic-based low-phase-noise photonic microwave generation. However, the previous reports on DM lasers [41,42] do not address the photonic microwave generation in optically injected DM lasers. Therefore, in this paper, we focus on photonic microwave generation based on the period-one dynamic of optically injected DM semiconductor lasers.…”
Section: Introductionmentioning
confidence: 99%
“…These salient features undoubtedly imply that DM lasers are a good candidate for P1-dynamic-based low-phase-noise photonic microwave generation. However, the previous reports on DM lasers [41,42] do not address the photonic microwave generation in optically injected DM lasers. Therefore, in this paper, we focus on photonic microwave generation based on the period-one dynamic of optically injected DM semiconductor lasers.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, the work in [18] reported that a tunable switching between the stable state and period-one state in an SL with OF can be achieved in a long-cavity region with about 10 m; it gives a potential application for square wave modulated photonic microwave generation. A very recent work [19] in 2021, demonstrated regular and irregular dynamics switching in a discrete-mode SL, also in a long-cavity region with about 32 m. The switching is found between stable state and period-one oscillation, as well as stable state and quasiperiod/chaotic oscillation. Such switching status-induced square wave signals provide a new way for generating clock signals required by high-speed signal processing and communication systems.…”
Section: Introductionmentioning
confidence: 90%
“…The index-patterned laser provides a distinct path to single-mode lasing, where the grating structure interacts with and enhances the device facet reflections, in contrast to laser devices that use distributed feedback mirrors or Bragg mirrors, and that rely on Bragg scattering. The unique spectral properties of index-patterned devices, particularly in the active regime, are coming under more intense study, as more exotic applications for laser devices are being sought with a growing application space in sensing, metrology and microwave photonics [8][9][10]. For creating integrated devices, a simple laser with an extremely high degree of frequency control is a boon.…”
Section: Introductionmentioning
confidence: 99%